The Meaning of Family Functioning on the Kindergarten Student’s Breakfast Pattern - Kumala Dewi, Endah; Asih Febriyanti , Dinni; Rusmawati, Diana (International Journal of Psychosocial Rehabilitation, 2020)
Objective of research: This research aims to finds the meaning of family functioning related to kindergarten students from middle and lower economic environments group. Method of research: Research I. Descriptive study about characteristics of parents, breakfast habits, and patterns of meeting children’s nutritional needs. The subject of the research is 29 students. The age characteristic of the subject is 5-6 years old. The data collection method uses a questionnaire. Data analysis technique: descriptive statistics. Research II. Case study and in-depth interviews. Participants: cadres, parents, headmaster, and health office staff. Data analysis technique: qualitative analysis. Results of the research: Based on the descriptive statistics analysis, most of the characteristics of parents’ work are laborers. Their education starts from elementary to secondary school level and their income is mostly under four million rupiah. The intake of vegetable and animal protein from the types of drinks and food consumed is estimated to still not meet the children’s nutritional needs. In case study, the researcher found a description of the meaning of family functioning in the development of several themes that ceased the provision of breakfast menus. The themes are permissive, discipline without knowledge, hand over parenting, and dependency on income. The development of the themes is influenced by the theme of care giving process and environmental involvement. Applications/Originality/Value: The meaning of family functioning shows the importance of the care giving process and environmental involvement.